Global Research Trends in Consumer Behavior and Sustainability in E-Commerce - Rita, Paulo (2022)
Rita, P., & Ramos, R. F. (2022). Global Research Trends in Consumer Behavior and Sustainability in E-Commerce: A Bibliometric Analysis of the Knowledge Structure. Sustainability, 14(15), 1-20. [9455]. https://doi.org/10.3390/su14159455 ---- Funding: Paulo Rita was supported through the FCT (Fundação para a Ciência e a Tecnologia) under UIDB/04152/2020—Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS